PENGEMBANGAN MEDIA SMART BOX BERBASIS QR CODE MATERI MENGENAL HAK DAN KEWAJIBAN ANAK DI KELAS VI UPTD SDN TANJUNG JATI 1 - Nurhalisa; Fachrur Rozie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employed a research and development (R&D) approach using the ADDIE model. The aim of this study was to develop a QR code-based smart box teaching aid on the topic of children’s rights and responsibilities that is valid, effective and engaging for Year 6 pupils at UPTD SDN Tanjung Jati 1. The subjects of this study comprised six Year 6 pupils in the small-group pilot test and 16 pupils in the large-group pilot test. Data collection techniques used included interviews, observation, questionnaires, and pre-test and post-test scores of student learning outcomes. The results of the study indicate that: 1) the QR code-based smart box media is valid for use, with validation scores of 96.67% from the media expert, 97.50% from the content expert, and 90.38% from the instructional design expert; 2) the results of the effectiveness trial, obtained from the teacher activity observation sheet, yielded percentages of 91.56% and 96.12% from the small-group and large-group trials respectively, both falling into the ‘highly effective’ category; the student activity observation sheet yielded a percentage of 85.19% and 86.45% of the results from the small-group and large-group trials fell into the ‘highly effective’ category; students’ traditional learning outcomes achieved a 100% pass rate in the ‘pass’ category; and the N-gain scores of 0.75 and 0.85 from the small-group and large-group trials, respectively, fell into the ‘high’ category, 3) The results of the appeal test, derived from teachers’ responses (85.42% and 87.50% for the small-group and large-group trials respectively), both fell into the ‘very appealing’ category, whilst students’ responses (86.67% and 97.03% for the small-group and large-group trials respectively) also fell into the ‘very appealing’ category. Based on the research results, the QR code-based smart box teaching aid on the subject of children’s rights and responsibilities meets the criteria of being highly valid, highly effective and highly engaging, and is therefore suitable for use in Year 6 at UPTD SDN Tanjung Jati 1.